Solving the Inverse Power Problem in Two-Tier Voting Settings - Matthias Weber (Tinbergen Institute, 2014)
There are many situations in which different groups make collective decisions by committee voting, where each group is represented by a single person. Theoretical concepts suggest how the voting systems in such committees should be designed, but these abstract rules can usually not be implemented perfectly. To find voting systems that approximate these rules the so called inverse power problem needs to be solved. I introduce a new method to address this problem in two-tier voting settings using the coefficient of variation. This method can easily be applied to a wide variety of settings and rules. After deriving the new method, I illustrate why it is to be preferred over more traditional methods.
Keywords: D71; D72; 330; inverse power problem; indirect voting power; two-tier voting; Penroses Square Root Rule